PERAN GURU DALAM MEMBERI MOTIVASI BELAJAR KEPADA SISWA PADA PEMBELAJARAN TEMATIK DI MADRASAH IBTIDAIYAH - Arif Prasetyo; Andi Prastowo (Mentari : Journal of Islamic Primary School, 2023)
Motivation is one of the psychological elements present in every student, so that to arouse students' enthusiasm for active learning, the role of the teacher in providing learning motivation is very important. One of the determinants of successful learning is the motivation that students possess. This research was conducted with the aim of: (1) Knowing and describing the role of teachers in motivating students' learning in thematic learning in grade V at Madrasah Ibtidaiyah (MI). (2) Knowing and describing the efforts of teachers in motivating students' learning in thematic learning in grade V at Madrasah Ibtidaiyah (MI). This research is a qualitative descriptive study using observation, interview, and documentation as data collection techniques. The results of this study state that: (1) The role of teachers in motivating students' learning in thematic learning in grade V at Madrasah Ibtidaiyah (MI) is demonstrated by the teacher as a demonstrator, classroom manager, mediator and facilitator, and evaluator. (2) Efforts made by teachers to motivate student learning include: a) The teacher as a demonstrator: using appropriate methods, using language that is easy to understand. b) The teacher as a classroom manager: paying attention to students' concentration, rolling seats. c) The teacher as a mediator and facilitator: providing learning media and facilities, playing movies. d) The teacher as an evaluator: giving rewards, giving grades or scores, giving praise and punishment.